Analytical Solution of Some Non – Linear Delay Differential Equations Using Adomian Decomposition Method - Jafaar Olasunkanmi Lawal; Muraina Sulyman; Risqot Garba Ibrahim; Faruk Muritala; Idris Seidu (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study examined some Non-linear Delay Differential Equation problems with known exact solutions and solved them using the Adomian Decomposition Method. We then observed the results and compared them with the corresponding exact solutions, and ultimately found that the two results agree. In addition, we discussed the phenomena that occur in real life and are described by Non-linear Differential Equations.